Ibudilast inhibits chemokine expression in rheumatoid synovial fibroblasts and exhibits immunomodulatory activity in experimental arthritis - Clanchy, F; Williams, R (Wiley, 2018)
Objective: Ibudilast is a well‐tolerated, orally available type 4 phosphodiesterase (PDE4) inhibitor used to treat asthma and stroke. As PDE4 inhibition suppresses inflammatory mediator production and cell proliferation in leukocytes, ibudilast may be a valuable therapy for the treatment of inflammatory auto‐immune diseases such as rheumatoid arthritis (RA). We assessed the therapeutic potential of ibudilast by measuring its capacity to modulate inflammation in human leukocytes, RA synovial fibroblasts (RASF) and in experimental arthritis. Methods: Using standard curve‐qPCR, the effect of ibudilast on gene expression in activated human leukocytes and RASF was measured. Ibudilast was used to treat DBA/1 mice with collagen‐induced arthritis and an adoptive transfer model was used to assess its tolerogenic capacity. Results: Ibudilast inhibited the expression of TNF, IL12A and IL12B, the secretion of TNFα and IL12/23p40 from leukocytes and reduced the expression of CCL5 and CCL3 in activated RASF. Treatment of experimental arthritis with ibudilast resulted in a reduction in IL‐17‐producing cells and inhibition of disease progression. When combined with a TNF‐inhibitor, ibudilast caused marked suppression of active disease. Exposure of leukocytes from type II collagen‐immunised DBA/1 mice to ibudilast in vitro attenuated their ability to adoptively‐transfer arthritis to DBA/1J‐PrkdcSCID mice, providing evidence of an immunomodulatory effect. Conclusion: Ibudilast reduced the expression and/or secretion of inflammatory mediators from activated human leukocytes and RASF, inhibited Th17 responses in vivo and improved established arthritis. Given the established safety profile of ibudilast in man, its clinical evaluation in RA, either alone or in combination with a TNF inhibitor, should be considered.